Snack food from unripe plantain and orange vesicle composite flour: nutritional and sensory properties - Adegunwa, M.O.; Fafiolu, O.F.; Adebowale, A.A.; Bakare, H.A.; Alamu, Emmanuel Oladeji (Informa UK Limited, 2019)
This study investigated the potential of unripe plantain (UP) and orange vesicle (OV) composite flour for cookies production. Proximate composition, functional properties, vitamins and mineral composition of the composite flour were carried out. Data obtained was subjected to Analysis of Variance. The addition of OV flour to UP flour increased protein (5.59–7.50%), fat (0.67–1.25%), ash (2.67–4.40%) and fibre (0.56–7.19%) contents, while moisture (9.10–7.43%), carbohydrate (81.05–72.39%) and energy (380.43–360.84 calories) contents decreased. Swelling capacity, solubility index and water absorption capacity increased while dispersibility decreased with OV flour inclusion. Addition of OV flour enhanced the minerals and Vitamin C contents of the flour blends and the resultant cookies produced. Overall sensory acceptability of the cookies from the flour blends showed that it was slightly preferred by the sensory panelist. It can be concluded that (UP-OV) composite flours could be used up to 60:40 ratios for producing cookies.